A statistical analysis of the social and environmental risks of the international trade in virtual water - Y. Kopnova (Cogent Economics & Finance, 2017)
This work develops a statistical methodology of analysis of the international trade in virtual water in the context of sustainable evolution. Using the example of agriculture, the impact of the flows of virtual water in the composition of products using indicators related to social and environmental risks was investigated. In the analysis data from websites of World Bank and the World trade organization for the period from 1996 to 2012 were used. The methodology was based on the toolkit of econometric modelling. The analysis showed the presence of stable groups of countries, including the groups of mainly exporting and mainly importing agricultural products. The share of the third group of countries with the varying sign of the balance of export and import amounted to only 30%. The factors influencing the formation of groups, in particular, were the role of water resources in terms of their scale and efficiency of use. The study of the impact of export and import of agricultural products on the indicators related to environmental and social risks identified significant problematic dependencies. The overall pattern for the three groups was that the countries with more intense trade flows had a lower rating of ecological sustainability.
Keywords: Q17; Q25; Q27; 330; virtual water; international trade; environmental risks; social risks; econometric model